ايجاد المؤشرات الكمية الملائمة لتقييم أداء النقل العام على الطرق الريفية حالة الدراسة: محور طرطوس-الدريكيش - أكرم رستم; هبه دغمه (Tishreen University, 2017)
تعاني معظم القرى والتجمعات الريفية عامةً، وفي محافظة طرطوس خاصةً، من سوء التنظيم للنقل وتخديم الناس، لدرجة أضحى بها التنقل بين الريف والمدينة معاناة كبيرة لأغلب المواطنين. يقدّم هذا البحث تقييماً لجودة النقل العام ضمن شبكة النقل الريفي بالاعتماد على مجموعة من المؤشرات والمعايير الكمية التي توضح لنا حالة أو مستوى نوعية خدمة النقل الريفي، وتحديد المعايير الأكثر تأثيراً وملاءمةً لعملية التقييم، واتخاذ إجراءات لزيادة فعالية أدائه. لقد أجريت الدراسة على محور طرطوس-الدريكيش الذي يمر في منطقة جبلية شديدة الانحدار في بعض المناطق، مما يجعل موضوع تحسين أداء منظومة النقل العام على هذا المحور مسألة مهمة تسهم في تيسير حركة المرور والنقل، وفي الاقلال من الحوادث على المفارق الكثيرة، وسيتم في هذا البحث تقديم التحليلات واستخلاص النتائج وتقديم الاقتراحات لمشكلة موضوع الدراسة. Most of the villages and rural communities are suffering, particularly in Tartous region, of poor organization of transport and serve the people. Therefore the movement between rural and city become a great suffering for most people. This research presents an evaluation the quality of public transport on rural transport network based on a set of indicators and quantitative criteria that show us the case or the quality of rural transport, And it identify the most effective and appropriate criteria to the evaluation operation. In addition, take procedure to increase the effectiveness of service performance. This study was conducted on Tartous- Al dreikish axis which passes in steep mountainous area in some areas is what makes the subject of improving the performance of the public transport system on this axis is an important issue contribute to facilitate the traffic and transport, and reducing accidents on the many junctions. In this research will be to provide analysis, draw conclusions and make suggestions to the problem in this study.